BACTERIOLOGICAL STUDY OF VENTILATOR-ASSOCIATED PNEUMONIA AND ANTIBIOTIC SUSCEPTIBILITY OF ISOLATES - KANIPAKAM, VIJAYA KUMAR; THOTI, HIMABINDU; SHARABU, YAMINI; VALLURI, ANITHA LAVANYA; GUNTI, RAJYALAKSHMI (International Journal of Current Pharmaceutical Research, 2024)
Objective: The present study determined the prevalence of various aerobic bacteria causing ventilator-associated pneumonia in adult patients. Initially the bacteria causing ventilator-associated pneumonia was isolated from ET samples and studied the antimicrobial susceptibility pattern of bacterial isolates. Methods: Total 250 endotracheal aspiration (ET) samples were collected from patients admitted in Medical, Respiratory and Surgical ICUs for 1 y period. ET aspirates were collected under aseptic precautions and processed as per standard operating procedure for the identification of microorganisms. The antibiotic susceptibility test was performed by using Kirby-Bauer disk diffusion method as per CLSI guidelines. Results: Out of the 250 samples processed, culture-positive were 34.8% (n=87) and culture-negative were 65.2% (n=163). Out of 87 culture-positive samples, polymicrobial growth was observed in 9.19% (n=8) and monomicrobial growth was observed in 90.8% (n=79). Gram negative bacilli 95.7% (n=91), and gram-positive cocci isolates are 4.2% (n=4). Among Gram-negative organisms isolated, A. baumannii is the most common isolate 33 (34.7%), followed by P. aeruginosa 28 (29.5%) and K. pneumoniae 20 (21.0%) E. coli 8 (8.4%) and E. cloacae 2 (2.1%). Out of 4 Gram-positive organisms isolated, 3 (3.1%) were MSSA, and 1(1.1%) was MRSA. Conclusion: VAP is increasingly associated with multidrug-resistant (MDR) pathogens due to the production of ESBL, Amp C b-lactamase, Metallo-b-lactamase. It is important to carry out aggressive surveillance to determine the prevalence of MDR organisms and to generate a local antibiogram periodically. Early and appropriate antibiotics in right doses followed by de-escalation based on microbiological culture results are essential to curtail the VAP rate. VAP bundle care shall be implemented correctly.